2021
DOI: 10.3390/diagnostics11060978
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FGFR4 Gene Polymorphism on the Progression of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a multifactorial malignancy, and its high incidence and mortality rate remain a global public health burden. Fibroblast growth factor receptor 4 (FGFR4) is a receptor tyrosine kinase that has been shown to play a key role in cancer development and prognosis via the activation of its downstream oncogenic signaling pathways. The present study aimed to explore the impact of FGFR4 gene polymorphisms on the risk and progression of CRC. Three FGFR4 single-nucleotide polymorphisms (SNPs), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
0
11
1
Order By: Relevance
“…Of the remaining 87 potentially eligible studies, 43 which did not meet the eligible criteria were further excluded. Finally, 44 studies were selected for the qualitative synthesis ( 9 , 12 – 18 , 21 , 23 27 , 34 – 45 , 47 53 , 55 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 87 potentially eligible studies, 43 which did not meet the eligible criteria were further excluded. Finally, 44 studies were selected for the qualitative synthesis ( 9 , 12 – 18 , 21 , 23 27 , 34 – 45 , 47 53 , 55 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, other researchers have reported contrasting results in several cancer types ( 43 46 ). There have also been many studies that failed to observe any significant contribution of the FGFR4 Gly388Arg SNP to the clinicopathological parameters or prognosis in patients with cancer ( 13 , 14 , 16 , 17 , 21 , 23 , 26 , 27 , 35 , 47 65 ). Therefore, the prognostic impact of the FGFR4 Gly388Arg polymorphism in cancer patients still remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Higher B-GAL activity reflects the ability of cancer to accelerate growth, invasion, metastasis and maturation. [32] Serum B-GAL activity is higher in colon cancer patients with a history of alcohol and nicotine dependence compared to colon cancer patients without a history of alcohol or tobacco use, and thus the prognosis may be poorer for patients with a previous history of tobacco and alcohol use, especially in those who have not quit smoking and alcohol during is disease course and postoperatively. [33] In addition, smoking may have an effect on serum levels of carcinoembryonic antigen, which may have an impact on prognosis, and it has also been shown that smoking suppresses the immune system and affects the functioning of immune cells, thus causing immune escape of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…FGF7, also called keratinocyte growth factor (KGF), is involved in inducing vascular endothelial growth factor (VEGF)-A expression, which plays important roles in the angiogenesis and metastasis of various cancer cells including colorectal cancer (51,52). FGFR4, a receptor tyrosine kinase, plays a key role in cancer development and prognosis via the activation of its downstream oncogenic signaling pathways (53).…”
Section: Discussionmentioning
confidence: 99%